The impact of KRAS mutations on the tumour microenvironment and treatment response in non-small cell lung cancer - Guomin Gu; Chunling Liu; Yan Yang; Yan Zhao; Xiaodan Zhu; Gang Sun (Polish Journal of Pathology)
Mutations in the KRAS gene in non-small cell lung cancer (NSCLC) are common drivers. Gene expression and mutation data of NSCLC were collected from the TCGA dataset. DEGs between KRAS mutations and wild type were identified, and enrichment analysis was performed. The differences in immune cell infiltration between the 2 groups were evaluated using ssGSEA, and TIDE scoring, immune checkpoint therapy sensitivity, and drug treatment sensitivity analysis were performed. The expression of PD-L1 and CTLA-4 in tumour tissues was detected by western blot. CD8+PD-1 and CD8+CTLA-4 cells were detected by flow cytometry. The frequencies of KRAS-G12C, KRAS-G12V, and KRAS-G12D mutations were the highest. A total of 1323 DEGs were predominantly enriched in the PI3K-Akt signalling pathway, cell adhesion molecules, and metabolism of xenobiotics by cytochrome P450. Additionally, most immune cell infiltration levels in KRAS mutations were lower than in KRAS wild type. Sensitivity to immune checkpoint inhibitors and drug treatments increased in KRAS mutations. Western blot revealed significantly higher expressions of PD-L1 and CTLA-4 in KRAS mutations compared to KRAS wild type. The infiltration of CD8+PD-1+ T cells and CD8+CTLA-4+ T cells was higher in KRAS mutations than in KRAS wild type. KRAS-G12C, KRAS-G12V, and KRAS-G12D mutations may enhance NSCLC drug resistance through immunosuppression.